(untitled) (Quaestiones Disputatae: temas en debate, 2017)
The article, framed in the context of a larger investigation, intends to give account of those influences that formed what is known as the New Political theory, proposed by the theologian Johann Baptist Metz. Beginning with an analytical reading according to the stages of the historical development of this theology, it will show which are the evolutionary processes that the theological principles presented as a critical reflection and as a world theology that sought the deprivitisation of the Christian faith and it’s position in the political experience through history.